Development of a novel platform for recombinant protein production in Corynebacterium glutamicum on ethanol - Xinyu Yu; Xiuxia Liu; Xiong Gao; Xunxun Luo; Yankun Yang; Ye Li; Chunli Liu; Chong Zhang; Zhonghu Bai (Synthetic and Systems Biotechnology, 2022)
Corynebacterium glutamicum represents an emerging recombinant protein expression factory due to its ideal features for protein secretion, but its applicability is harmed by the lack of an autoinduction system with tight regulation and high yield. Here, we propose a new recombinant protein manufacturing platform that leverages ethanol as both a delayed carbon source and an inducer. First, we reanalysed the native inducible promoter PICL from the acetate uptake operon and found that its limited capacity is the result of the inadequate translation initial architecture. The two strategies of bicistronic design and ribozyme-based insulator can ensure the high activity of this promoter. Next, through transcriptional engineering that alters transcription factor binding sites (TFBSs) and the first transcribed sequence, the truncated promoter PA256 with a dramatically higher transcription level was generated. When producing the superfolder green fluorescent protein (sfGFP) under 1% ethanol conditions, PA256 exhibited substantially lower protein accumulation in prophase but an approximately 2.5-fold greater final yield than the strong promoter PH36. This superior expression mode was further validated using two secreted proteins, camelid antibody fragment (VHH) and endoxylanase (XynA). Furthermore, utilizing CRISPRi technology, ethanol utilization blocking strains were created, and PA256 was shown to be impaired in the phosphotransacetylase (PTA) knockdown strains, indicating that ethanol metabolism into the tricarboxylic acid cycle is required for PA256 upregulation. Finally, this platform was applied to produce the “de novo design” protein NEO-2/15, and by introducing the N-propeptide of CspB, NEO-2/15 was effectively secreted with the accumulation 281 mg/L obtained after 24 h of shake-flask fermentation. To the best of our knowledge, this is the first report of NEO-2/15 secretory overexpression.